PENGARUH KEBIJAKAN MANAJEMEN KEUANGAN TERHADAP NILAI PERUSAHAAN SEKTOR PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2021 - Sari, Elina Mutia (Universitas Mitra Indonesia, 2024)
Financial management policies are divided into two parts, the first is funding decisions and dividend policies. Funding decisions can be interpreted as decisions concerning the company's financial structure (financial structure). Dividend policy is the distribution of operating results or profits given to shareholders, usually in the form of cash dividends and retained earnings. This study aims to determine whether funding decisions and dividend policy have a simultaneous effect on firm value in the property sector listed on the Indonesia Stock Exchange. the type of data source used in this study is secondary data. The data collection technique in this study is to use documentation data collection techniques and literature study. The sampling procedure used in this study is non-probability with a purposive sampling technique. The method of analysis uses the classical assumption test, multiple linear regression analysis, hypothesis testing, and Determinant Coefficient tests. Based on the results of the analysis concluded that funding decisions and dividend policy simultaneously have a significant and significant effect on firm value. And partially funding decisions and dividend policies each affect firm value